Transtornos afetivos em idosos brasileiros: análise das tendências de mortalidade, morbidade e custos de serviços de saúde - Praia, Raquel de Souza (2018)
Affective disorders (AD), including depression have important epidemiological impact on elderly morbi-mortality been also associated to elevate suicide rates. However, AD impact on trends elderly mortality, morbidity and Brazilian health service cost (hospitalization and outpatient care) need to be more deeply investigated. Therefore, this study evaluated the trends of AD and suicide mortality in Brazilian elderly population (1996-2015) and in use of health services (hospitalization and outpatient care) and their costs in 2009 to 2015 period by a socio-ecological analysis using databank evaluable for Health Unic System (DATASUS, Brazil Ministry). The study was performed just in elderly subjects (> 60 years old) considering as co-variables: sex and age. Linear, jointpoint and multivariate regressions were used to detect change in the trends of AD and suicide mortality. Total AD mortality was slightly higher in women (1.2/100.000) than men (1.0/100.000). At contrary, suicide mortality rate was higher in men (13.5/100.000) than females (2.5/100.000). In both mortality causes, occurrence was age-dependent, with higher rates in oldest-old group (> 80 years). Hospitalizations by AD were also higher in older group, in both sex. However, hospitalization costs trend to decrease in the last four years. The whole of results suggests the necessity to construct specific preventive and treatment programs for elderly people, since this population presents important biological, functional, health and social specificities that are different of find in adults.